Effects of environmental factors on morphological and quality parameters of table beet root - Takácsné Hájos, M.; Rubóczki, T. (International Journal of Horticultural Science, 2012)
In our trial morphological and quality parameters of 15 table root varieties were tested at 3 different sowing dates: 15 April, 9 July and 19 August 2010. In the trials the root shape of the varieties form the April sowing date approached most the regular spherical shape (diameter/length –1.0) which is favoured both by fresh market and the processing industry. In the July and August sowings the roots were elongated with reduced proportions. The highest red pigment content (betacyanin) was observed in the second sowing of July (>80 mg/100 g). In the late sowing (August, under plastic tent) a further 10–20 mg/100 g pigment increase was measured in relation to the earlier sowing dates of the same varieties. A similar trend could be observed in yellow pigments (vulgaxanthis) which proves a close correlation between the quantities of the 2 pigments (r=0.823). The highest vulgaxanthin content (103.3–124.18 mg/100 g) was obtained form roots of the late sowing harvested in December. Varieties reacted differently to temperature and so to sugar accumulation in the different sowing periods. In the July sowing higher water soluble solids content was measured on the mean of varieties (10.12 %) as compared to the April sowing (7.76%). Sensory evaluations included inner colour intensity (1–5), with ring (1–3) and taste (1–5) of the raw material evaluated by scoring. According to laboratory measurements better inner colour intensity was observed in the July and August sowing dates. In these samples uniformly coloured, almost with, ring-free roots were obtained. In our trial varieties from the spring sowing had superior taste. Early sowing is recommended for fresh market sale while the second crop (July) harvested in autumn can satisfy processing requirements. In the late sowing (under unheated plastic tent) fresh beet root can be grown at the end of autumn or beginning of winter, thus prolonging the usability of plastic tents.